Matharpacady-11.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
A coconut vendor outside Mary Lodge, commonly referred to as David and Stanny’s house. The ground floor of the bungalow still has vestiges of classroom numbers from the time St. Isabel’s Primary School was established here to promote female education. The school was set up by the Ladies Charitable Association, Mazagaon Circle, and the first class took place on 9th November 1887, with 40 students and two teachers. Later St. Isabel’s Primary School relocated to Tank Square, and thereafter, Mount Road (39, Dr Masceranhas Road), where it stands now.